Effects of early-life stress on cognitive function and hippocampal structure in female rodents. (7th February 2017) - Loi, M.; Mossink, J.C.L.; Meerhoff, G.F.; Den Blaauwen, J.L.; Lucassen, P.J.; Joëls, M.
Highlights: Effects of early stress were studied on later hippocampal structure and function. To rescue these effects, 50% were treated with a GR blocker during puberty. Neither early stress nor GR blockade affected behavioral performance in female rats. Also, dentate gyrus structure, proliferation and neurogenesis did not differ. As confirmed by literature, females may be more resilient to early-life stress. Abstract: We tested the effect of early-life stress (ELS) – 24 h maternal deprivation (MD) at postnatal day (PND) 3 – on cognitive performance and hippocampal structure in 12–17-week-old female rats. Behavioral performance was examined in: the Elevated Plus Maze, as an index for general anxiety; the rodent Iowa gambling test, probing reward-based decision making; and the object recognition and object-in-location task, to assess non-stressful contextual memory performance. We further determined hippocampal dentate gyrus (DG) volume and cell density as well as adult proliferation and neurogenesis rates. Half of the rats was treated with the glucocorticoid receptor antagonist mifepristone during a critical pre-pubertal developmental window (PNDs 26–28), in an attempt to ameliorate the potentially adverse behavioral consequences of ELS. Neither MD nor treatment with the glucocorticoid antagonist affected behavioral performance of the females in any of the tasks. Also, DG structure, proliferation and neurogenesis were not different between the groups. Lack of structural differences and a behavioral phenotype in non-stressful hippocampus dependent learning tasks fits with the lack of phenotype generally reported after ELS in female but less so in male rodents. As evident from an extensive literature review, female and male animals appear to respond more similarly to early-life adversity when tested in anxiety-related tasks. This agrees with recent findings in humans suggesting that females may be relatively resilient to the structural/hippocampal effects of childhood maltreatment, but not to the anxiety and mood-related psychopathology for which childhood maltreatment is considered a risk factor.